Метод оценки критериев затопления промплощадки Запорожской АЭС при запроектных землетрясениях - Скалозубов, В.И.; Богодист, В.В.; Козлов, И.Л.; Габлая, Т.В.; Кочнева, В.Ю. (Ядерна та радіаційна безпека, 2013)
Предложена гидродинамическая модель возможного затопления промплощадки
Запорожской АЭС при запроектных землетрясениях и смерчах. В отличие от
квазистационарного подхода стресс-тестов, в предложенной модели учитывается
динамический характер процессов затопления, а также непосредственное влияние
внешних экстремальных воздействий на Каховское водохранилище. В результате
проведенного гидродинамического моделирования определены возможные условия
и критерии затопления промплощадки ЗАЭС при внешних экстремальных воздействиях. Запропоновано гідродинамічну модель можливого затоплення проммайданчика
Запорізької АЕС у разі позапроектних землетрусів та смерчів. На відміну від
квазістаціонарного підходу стрес-тестів, у запропонованій моделі враховується
динамічний характер процесів затоплення, а також безпосередній вплив зовнішніх
екстремальних дій на Каховське водосховище. В результаті проведеного
гідродинамічного моделювання визначено можливі умови та критерії затоплення
проммайданчика ЗАЕС під час зовнішніх екстремальних впливів. Flooding of the NPP site because of a beyond design basis earthquake followed by a
tsunami was one of the principal causes of the Fukushima Daiichi accident. The National StressTest
Report of Ukraine indicates that such events are unlikely to occur at sites of Ukrainian
NPPs. However, the methodology used in stress tests has been insufficiently proved as long as it
considers quasistationary processes of propagation of a possible flooding wave.
The paper offers a hydrodynamic model of possible flooding of the Zaporizhzhya NPP
site during beyond design basis earthquakes and tornadoes. Unlike the quasistationary approach
of stress tests, the model takes into account the dynamic nature of flooding processes and direct
effects of external hazards on the Kakhovka Reservoir.
The results of the hydrodynamic modeling are possible conditions and criteria of flooding
for the Zaporizhzhya NPP site under external hazards